Expression of SOLOIST/MRTFB i4, a novel neuronal isoform of the mouse serum response factor coactivator myocardin‐related transcription factor‐B, negatively regulates dendritic complexity in cortical neurons. Issue 4 (31st July 2020) - Ishibashi, Yuta; Shoji, Shizuku; Ihara, Daisuke; Kubo, Yukimi; Tanaka, Takuro; Tanabe, Hiroki; Hakamata, Tomoyuki; Miyata, Tomoaki; Satou, Natsumi; Sakagami, Hiroyuki; Mizuguchi, Mineyuki; Kikuchi, Keietsu; et al.
Abstract: Megakaryoblastic leukemia 2 (MKL2)/myocardin‐related transcription factor‐B (MRTFB), a serum response factor (SRF) coactivator, is an important regulator of gene expression and neuronal morphology. Here, we show that different mouse MRTFB splice isoforms, including a novel fourth MRTFB isoform named spliced neuronal long isoform of SRF transcriptional coactivator (SOLOIST)/MRTFB isoform 4 (MRTFB i4), play distinct roles in this process. SOLOIST/MRTFB i4 has a short exon that encodes 21 amino acid residues ahead of the first RPXXXEL (RPEL) motif in MRTFB isoform 3. Quantitative PCR revealed that SOLOIST/MRTFB i4 and isoform 1 were enriched in the forebrain and neurons, and up‐regulated during brain development. Conversely, isoform 3 was detected in various tissues, including both neurons and astrocytes, and was down‐regulated in the developing brain. Reporter assays supported the SRF‐coactivator function of SOLOIST/MRTFB i4 as well as isoform 1. Acute expression of MRTFB isoform 1, but not isoform 3 or SOLOIST/MRTFB i4, in neuronal cells within 24 hr drastically increased endogenous immediate early gene [c‐ fos, egr 1, and activity‐regulated cytoskeleton‐associated protein] expression, but not endogenous actinin α1, β‐actin, gelsolin, or srf gene expression measured by qPCR. Over‐expression of SOLOIST/MRTFB i4 reduced the dendritic complexity of cortical neurons, whereas over‐expression of isoform 1 increased this complexity. Co‐expression of isoform 1 and SOLOIST/MRTFB i4 in cortical neurons revealed that isoform 1 competitively counteracted down‐regulation by SOLOIST/MRTFB i4. Our findings indicate that MRTFB isoforms have unique expression patterns and differential effects on gene expression and dendritic complexity, which contribute to shaping neuronal circuits, at least in part. Abstract : Myocardin‐related transcription factor (MRTF) is a serum response factor (SRF) coactivator. We identified the novel and neuronal MRTFB isoform, spliced neuronal long isoform of SRF transcriptional coactivator/MRTFB isoform 4 (SOLOIST/MRTFB i4). We found a reduction in dendritic complexity by SOLOIST/MRTFB i4 over‐expression, which was counteracted by MRTFB isoform 1 that increases dendritic complexity. These findings may contribute to a better understanding of neuronal plasticity, such as fine‐tuning of dendritic morphology by the existence of multiple isoforms, and may help elucidate the mechanism underlying the disruption of this process in neurological disorders.